Determinants of dividend payout ratio: evidence from Indonesian manufacturing companies - Dessy Widyawati; Astiwi Indriani (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2019)
The purpose of this study is to investigate and analyze the relationship between return on assets, growth sales, debt to equity ratio, lagged dividend to dividend payout ratio and size as control variable. Data collected from manufacturing industries in Indonesian Stock Exchange 2011-2017. The method of this study is ordinary least square regression. The results of this study shows that return on assets and lagged dividend have positive impact to dividend payout ratio. Growth sales has insignificance negative relationship to dividend payout ratio. Debt to equity ratio has positive relationship to dividend payout ratio and has insignificance sign